The Influence Of Profit And Operational Performance Of Regionally-Owned Enterprises On Regional Original Income In Badung Regency - Ni Made Tia Aditya Putri; Shelly Kristina Yacobus D Lomo; Komang Ayu Dealova; Anisa Safitri Ramadani; Erwinsyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to empirically examine the effect of profit and operational performance of Regionally-Owned Enterprises (BUMD) on Regional Original Revenue (PAD) in Badung Regency. This study is based on a research gap in previous studies. Some studies place BUMD profit as the dominant factor in increasing PAD, while others emphasize that operational aspects and management efficiency of regional companies contribute more significantly to increasing regional revenue. The data used in this study comes from the financial reports of BUMDs in Badung Regency for the 2019–2023 period and were analyzed using multiple linear regression with SPSS version 27 software. The analysis results indicate that profit and operational performance simultaneously have a significant effect on Badung Regency's PAD, as reflected in the coefficient of determination (R²), which indicates the model's ability to explain variations in PAD between periods. Partially, operational performance is proven to have a positive and significant effect on PAD, while profit shows a positive but insignificant effect. These findings confirm that the effectiveness of BUMD operational management plays a greater role than accounting profit in driving PAD growth. Practically, the results of this study provide implications for local governments and BUMD management to place greater emphasis on strategies to increase operational efficiency, strengthen corporate management practices, and optimize service quality in order to maximize BUMD's contribution to PAD and support sustainable regional economic development.